Extrato de Ocimum basilicum l. no procedimento adesivo em dentina hígida e erodida - Estellita, Maria Clara Ayres (2024)
The use of polyphenols in adhesive procedure has shown to be very promising in reducing degradation pathways of the hybrid layer in addition to reinforcing the collagen matrix. Thus, the objective of the present work was to evaluate in vitro the effect of different concentrations of the aqueous extract of Ocimum basilicum L., popularly known as basil, as a pre-treatment of the adhesive procedure (Adapter Single Bond 2) on healthy human dentin and eroded with 1% citric acid. The independent variables under investigation were: distilled water [DW]; grape seed extract 6.5 m/v% [GSE 6.5%]; OB extract 0.1 m/v% [OB 0.1%]; OB extract 1 m/v% [OB 1%] and OB extract 10 m/v% [OB 10%], as pre-treatments actively applied for 1 minute on sound and eroded dentin 3 times a day for 5 consecutive days using 1% citric acid. The chemical characterization of the extracts was carried out through the quantification of total phenolic compounds using gallic acid as a standard in addition to measuring their respective pH with a pHmeter. Furthermore, in situ degree of conversion (DC) was evaluated using a micro-Raman spectrometer (n=3) and bond strength using a microtensile test, carried out on a universal testing machine (n=8) and by analyzing the fracture pattern (FP) using a stereoscopic magnifying glass. These analyzes were carried out after 24 hours of storage in distilled water at 37°C and after 5,000 thermocycling cycles with tanks at 5 and 55°C and immersion for 30 seconds. The data obtained from the DC were subjected to the Shapiro-Wilk normality test and then to one-way ANOVA, while the data relating to microtensile test, after checking normality, were subjected to two-way ANOVA and Tukey's post-test, while the results of the fracture pattern analysis were subjected to the Chi-square test, all with a significance level of 5%. The quantification of phenolic compounds indicated that the OB extract has 91.8 ± 1.46 mg equivalent of gallic acid per gram, while the GSE has 207.9 ± 7.83 and its pHs were, respectively, 5.47 and 4 ,9. The experimental groups did not show a significant difference between themselves in the DC (p= 0.272). With regard to bond strength, it was possible to observe that, in sound dentin, OB 1% (48.4 ± 8.0) presented superior results to the others, being statistically similar to OB 10% (40.5 ± 6.0, 9), which, in turn, was similar to the other groups and the only group that showed a decline in resistance after thermocycling was DW (p< 0.05). In eroded dentin, GSE 6.5 showed better results in 24 hours, (29.4 ± 9.8) being statistically similar to OB 0.1% (24.8 ± 5.9) and OB 1% (22.3 ± 4.3) and, after thermocycling, GSE 6.5% (32.3 ± 8.5) remained statistically similar to OB 0.1% (p< 0.05). Regarding FP, no statistical difference was observed between pre-treatments. Thus, it was possible to conclude that OB 1% was better pre-treatment in healthy dentin, while GSE 6.5% and OB 0.1% stood out in eroded dentin.